Rastin Group Funding (RGF): A Financial Subsystem of Rastin Banking - Bidabad, Bijan (International Journal of Islamic Banking and Finance Research, 2019)
Rastin Group Funding (RGF) makes mobilization of limited and determined depositor’s resources for a specific project possible and shares depositors in the outcome of the projects with the intent of benefit and via the bank according to Rastin Banking rules. In Rastin Group Funding, after evaluation of the project proposal, and by observing the rules of the PLS Base System or the applied Financial Subsystem defined in Rastin Banking and considering the Rastin Banking Executive Bylaw; bank mobilizes the pre-specified depositors’ resources for a specific project; and after receiving necessary collaterals and guarantees allocates them to entrepreneur and performs supervision over the project execution. Bank receives capital management fee by supplying capital management services to depositors.